Computational analysis of nonenzymatic deamidation of asparagine residues catalysed by acetic acid. (3rd July 2021) - Nakayoshi, Tomoki; Wanita, Kota; Kato, Koichi; Kurimoto, Eiji; Oda, Akifumi
Abstract : In peptides and proteins, nonenzymatic deamidation of asparagine (Asn) residues can trigger some age-related diseases by disrupting the conformation of the biological proteins. In addition, Asn-residue deamidation, which has been observed in various protein preparations, is an important determinant of the quality of protein preparations. In the present study, we investigated the molecular mechanisms of Asn-residue deamidation catalysed by acetic acid, which is frequently used as a buffer in protein preparations. The calculations were conducted using an Asn residue capped with acetyl and methylamino groups on the N- and C-termini, respectively. Energy minima and transition-state geometries were optimised using B3LYP density functional theory (DFT) calculations. The relative energies of all optimised geometries obtained by the MP2 single-point energy calculations were corrected for zero-point energies calculated using the B3LYP DFT method. Asn-residue deamidation was divided roughly into two processes (cyclisation and deammoniation). Computational results indicate that cyclisation is rate-determining. A catalytic acetic acid molecule acted as a proton-transfer mediator in both processes. These results provide useful information for improving formulations of protein preparation. GRAPHICAL ABSTRACT: UF0001